(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of the Google Sheets platform integrated with ChatGPT in detecting drug interactions and contraindications in outpatient prescriptions at Transport Hospital.Methods: A quasi-experimental before–after study was conducted from April 4, 2025, to July 4, 2025. The study analyzed 1,476 outpatient prescriptions containing two or more medications and surveyed 50 healthcare professionals using the tool.Results: The tool enabled batch processing of prescriptions, increasing review capacity from 78 prescriptions/hour (manual) to unlimited. The detection rate of contraindicated interactions rose from 0.41% to 0.75%, and prescriptions requiring modification increased 1.67-fold. Survey results from 50 healthcare professionals indicated an average satisfaction score of 4.2/5; 92% rated the tool as useful and 84% expressed willingness to continue its use. Conclusion: The integration of Google Sheets with ChatGPT significantly improved the efficiency and quality of drug interaction screening under resource-limited conditions, with positive user feedback supporting its feasibility and long-term clinical application. Further research should expand the input database and integrate real-time alerts into electronic prescribing systems.